Mathematical Education in Early Christian Authors - Larionova, Sofia (Hyperboreus, 2023)
When mathematical sciences started their advancement into non-professional education, it became necessary to explain why these sciences should be studied by those who are not going to become professional mathematicians. The ancients found various arguments in favor of studying mathematical sciences. For example, there were arguments of an utilitarian nature: the beneﬁts of mathematics were seen in its application in trade, navigation, managing one’s estate, etc. There were also those who prioritized the beneﬁts of mathematics for the development of intelligence: mathematics is useful because it exercises the mind. According to others, the main beneﬁt of studying mathematics is that it promotes the acquisition of various virtues (for example, justice and moderation), and also serves as a preparation for the study of dialectics (and later, Holy Scripture). This argument was borrowed in one form or another by Christian authors from pagans. The article traces how Philo of Alexandria and the following Christian authors (namely, Clement and Origen) justify the need to study mathematics, how their argumentation correlates with the ancient pagan tradition, and also what conclusions about the practice of teaching mathematical disciplines and their content follow from their testimonies. The article shows that, according to the views of the above-mentioned authors, there were important internal reasons linking mathematics with the concept of God, which could encourage the study of mathematics among Christians. It was not just about the ability of mathematics to exercise the mind, or about the important role of mathematics in gaining access to the unconditional truths of the Platonic tradition, but, more importantly, God himself is connected with the mathematical categories of numbers, measures and weights, which made theological interpretations of mathematics possible.